Transcriptome analysis and identification of genes associated with leaf crude protein content in foxtail millet [Setaria italica (L.) P. Beauv.] - Cui, Yanjiao; Liu, Dan; Zhao, Zilong; Zhang, Jing; Li, Suying; Liu, Zhengli (Frontiers in Genetics, 2023)
Spruce spider mite is a primary insect pest of Chinese chestnut in China and seriously influences its yield and quality. However, the current management against this mite is costly and poorly effective. In previous research, we bred several foxtail millet materials for interplanting with chestnut tree, and found that they had high levels of crude protein (CP) in leaves and attracted spruce spider mite to feed on the leaves, thereby reducing chestnut damage. In this study, four foxtail millet varieties with significant differences in leaf CP content were used for high-throughput sequencing, and 435 differentially expressed genes (DEGs) were identified, suggesting their potential role in CP accumulation. Gene enrichment analyses were carried out to comprehend the functions of these genes and the biological processes in which they are involved. Some DEGs were found to be associated with nitrogen metabolism and ubiquitin-mediated proteolysis pathways. In addition, transcription factors (TFs) were evaluated; we identified 40 TF genes categorized into 11 TF families. Our findings represent an important resource that clarifies the mechanisms of accumulation and control of leaf CP in foxtail millet, and provide an opportunity for suppression of spruce spider mite attack on Chinese chestnut by interplanting with foxtail millet varieties with high concentrations of leaf CP.